Effect of titin phosphorylation on degradation of titin from skeletal muscles - Ying Wang; Xin Li; Dequan Zhang; Zheng Li; Baocai Xu; Jie Zhu (Food Science and Human Wellness)
The degradation of titin could make the myofibrillar fragmentation to improve meat tenderization during postmortem. This study aimed to investigate effect of phosphorylation on titin degradation. Protein kinase A (PKA) and alkaline phosphatase (AP) were added to crude titin extracted from ovine longissimus lumborum (LL) muscles. Phosphorylated/dephosphorylated titin were incubated with μ-calpain at 4 °C for 2 days. Results showed titin in AP group started degradation earlier than that in PKA and control groups. There were 20, 16 and 12 phosphorylated sites identified by iTRAQ in the PKA, control and AP group, respectively. 3D structure of dephosphorylated titin fragment was simulated and its molecular dynamics trajectory analysis was performed using Discovery StudioTM. The dihedral angle in AP group was less and the dephosphorylated fragment had a higher kinetic energy and total energy. We suggested that changes caused by AP treatment might make titin unstable, which easily degraded by μ-calpain.